The Economics of Two-way Interconnection - Berger, Ulrich (Forschungsergebnisse der Wirtschaftsuniversitaet Wien, 2006)
For his research on the topic of this book Ulrich Berger was awarded the Research Prize of the Vodafone Foundation and the WU Best Paper Award. This book studies the economics of telecommunications networks characterized by two-way interconnection. Special emphasis is put on the role of access charges. Starting from the standard model used in the literature on network competition, the effect of departing from three of this model's less realistic assumptions is investigated. First, call externalities are integrated into the model. Secondly, competition between three or more networks is studied in a dynamic setting. Finally, a local interaction structure between agents is introduced to replace the unrealistic assumption of balanced calling patterns. In each of these cases, some of the conventional wisdom on the role of access charges is overturned by new results.